2013
DOI: 10.1111/bjd.12377
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenFOXP3polymorphisms and vitiligo in a Han Chinese population

Abstract: FOXP3 gene polymorphisms contributed to vitiligo risk in a Han Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 33 publications
3
74
2
Order By: Relevance
“…Similarly, the rs2232365 GG genotype was considered a risk factor for vitiligo patients in a Han Chinese population. Indeed, significantly increased vitiligo risk was associated with the rs2232365 GG [odds ratio (OR) 1.68, 95 percent confidence interval (CI) 1.17 -2.39, P = 0.004] (28).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the rs2232365 GG genotype was considered a risk factor for vitiligo patients in a Han Chinese population. Indeed, significantly increased vitiligo risk was associated with the rs2232365 GG [odds ratio (OR) 1.68, 95 percent confidence interval (CI) 1.17 -2.39, P = 0.004] (28).…”
Section: Discussionmentioning
confidence: 99%
“…27 Song et al 13 suggested that it appears that defective CTLA4 expression, function or both are associated with autoimmune diseases including vitiligo. Beside, we did not find an association of genoytpe and allele frequencies for rs231775 polymorphism with vitiligo patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,11,13 indicates that genetic factors play a role in pathogenesis of the disease. 30 Nath et al 31 reported that the relative risk of vitiligo for the first degree relatives of patients increased by at least 7-10 fold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms in these regions could affect binding capability for transcription factors and, hence, FOXP3 expression and Treg function ). Among the polymorphisms described in regulatory regions of FOXP3, rs2232365 (A to G) has been associated with immunologic diseases such as vitiligo (Song et al 2013) and psoriasis (Song et al 2012), highlighting its importance in Treg function, but has been poorly investigated in cancers. Though chromosomal alterations are often seen in HM, they do not encompass all HM cases and are observable only after disease onset, highlighting the importance of studying inherited genetic polymorphisms, such as SNPs, which may play a role in HM susceptibility, onset and/or progression.…”
Section: Introductionmentioning
confidence: 99%